Kajian Bio-Korosi pada Struktur Beton di Lingkungan Industri Kota Lhokseumawe akibat Emisi Senyawa Fosfor - Tanjung, Aisyah Protonia; Wardani, Lusyana Eka (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Concrete is a construction material widely used in infrastructure development due to its high compressive strength and good resistance to various environmental conditions. However, in industrial environments, concrete is susceptible to degradation caused by chemical and biological processes, one of which is bio-corrosion. Bio-corrosion occurs as a result of the activity of acid-producing microorganisms that lower the pH of the concrete surface, damage the material matrix, and accelerate corrosion of the reinforcing steel. Industrial areas, such as regions with fertilizer plants and chemical industries, generate emissions and waste containing phosphorus compounds that can affect the durability of concrete. Phosphorus compounds play a dual role: they can accelerate bio-corrosion by serving as a nutrient source for microorganisms, yet under certain conditions they may also act as corrosion inhibitors by forming protective layers on reinforcing steel. This study aims to comprehensively examine the role of phosphorus compounds in concrete bio-corrosion within industrial environments. The method employed is a literature review that analyzes previous studies addressing bio-corrosion mechanisms, microbial activity, and the influence of phosphorus on concrete and reinforcing steel. The results indicate that concrete bio-corrosion is a complex phenomenon influenced by interactions among biological, chemical, and environmental factors. The role of phosphorus is highly dependent on the surrounding environmental conditions of the concrete; therefore, effective industrial environmental management is a crucial factor in maintaining the durability and service life of concrete structures. This review is expected to provide a scientific basis for mitigating concrete deterioration and supporting sustainable infrastructure management in industrial areas.